strategi, flipped classroom STRATEGI PEMBELAJARAN FLIPPED CLASSROOM PADA MATA KULIAH SASTRA ANAK UNIVERSITAS NEGERI SURABAYA DENGAN METODE THINK PAIR SHARE - Desy Antikasari; Titik Indarti; Resdianto Permata Raharjo (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
Flipped Classroom is a reverse classroom learning that was implemented for the first time during the covid-19 pandemic. The learning strategy can be developed in the independent learning program. This strategy is supported by the Think Pair Share method. The role of a lecturer is able to direct students to be more active in learning and not only passively receive material. One of the goals of using the Flipped Classroom learning strategy is to build motivation and critical thinking for a student in an increasingly sophisticated digital era to study Children's Literature courses. This study uses a qualitative method that contains a descriptive narrative data description. The study used is more directed to the study of documents/texts. The data analysis techniques used are data identification, data classification, data analysis, data exposure, and data verification. The object of this research is a document or journal containing the Flipped Classroom learning strategy with the researcher's own subject. Keywords: strategy, flipped classroom